PENDIDIKAN SENI RUPA BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI MELALUI PEMBELAJARAN SENI MEDIA BARU - Denny Wahyu Triawan (Universitas Islam Nahdlatul Ulama Jepara, 2026)
The development of contemporary art demands a paradigm transformation in art education, particularly in integrating information and communication technology (ICT) as a learning medium. New media art emerges as an artistic expression that utilizes digital technology, computers, and communication networks as tools, media, and sources of creative ideas. This article conceptually examines how new media art learning can become an innovative alternative in ICT-based fine arts education in Indonesia. Through a literature review of the historical development of new media art in the West and Indonesia, as well as analysis of recent research (2018–2026) on ICT integration in art education, this article identifies the pedagogical potential of new media art in developing students' creativity, aesthetic appreciation, digital literacy, and 21st-century skills. The findings indicate that implementing new media art in the fine arts education curriculum requires teacher creativity in designing contextual learning methods, cross-disciplinary collaboration, and adequate technological infrastructure support.